Inoculation Eschars and Fever: A Case of African Tick Bite Fever - Bouceiro-Mendes, R. (2019)
African tick bite fever is caused by the intracellular bacteria Rickettsia africae. This bacterium is transmitted through the bite of the Amblyomma tick, which carries a high rate of R. africae infection. African tick bite fever is the second most frequent cause of fever in travelers returning from sub-Saharan Africa.We present the case of a 58-year-old man, returning from South Africa, with a three-day history of fever, generalized headache and cervical myalgia. On physical examination multiple inoculation eschars and tender inguinal lymph nodes were documented.Histological examination of a skin lesion was compatible with spotted fever and the diagnosis of R. africae infection was confirmed through polymerase chain reaction analysis.The global increase in international tourism, particularly to remote areas, predisposes to tick bites. In febrile tourists returning from endemic areas and after a thorough clinical examination, the diagnosis of African tick bite fever should be born in mind.